End‐diastolic segmentation of intravascular ultrasound images enables more reproducible volumetric analysis of atheroma burden. Issue 3 (17th August 2021) - Erdogan, Emrah; Huang, Xingru; Cooper, Jackie; Jain, Ajay; Ramasamy, Anantharaman; Bajaj, Retesh; Torii, Ryo; Moon, James; Deaner, Andrew; Costa, Christos; Garcia‐Garcia, Hector M.; Tufaro, Vincenzo; et al.
Abstract: Background: Volumetric intravascular ultrasound (IVUS) analysis is currently performed at a fixed frame interval, neglecting the cyclic changes in vessel dimensions occurring during the cardiac cycle that can affect the reproducibility of the results. Analysis of end‐diastolic (ED) IVUS frames has been proposed to overcome this limitation. However, at present, there is lack of data to support its superiority over conventional IVUS. Objectives: The present study aims to compare the reproducibility of IVUS volumetric analysis performed at a fixed frame interval and at the ED frames, identified retrospectively using a novel deep‐learning methodology. Methods: IVUS data acquired from 97 vessels were included in the present study; each vessel was segmented at 1 mm interval (conventional approach) and at ED frame twice by an expert analyst. Reproducibility was tested for the following metrics; normalized lumen, vessel and total atheroma volume (TAV), and percent atheroma volume (PAV). Results: The mean length of the analyzed segments was 50.0 ± 24.1 mm. ED analysis was more reproducible than the conventional analysis for the normalized lumen (mean difference: 0.76 ± 4.03 mm 3 vs. 1.72 ± 11.37 mm 3 ; p for the variance of differences ratio < 0.001), vessel (0.30 ± 1.79 mm 3 vs. −0.47 ± 10.26 mm 3 ; p < 0.001), TAV (−0.46 ± 4.03 mm 3 vs. −2.19 ± 14.39 mm 3 ; p < 0.001) and PAV (−0.12 ± 0.59% vs. −0.34 ± 1.34%; p < 0.001). Results were similar when the analysis focused on the 10 mm most diseased segment. The superiority of the ED approach was due to a more reproducible detection of the segment of interest and to the fact that it was not susceptible to the longitudinal motion of the IVUS probe and the cyclic changes in vessel dimensions during the cardiac cycle. Conclusions: ED IVUS segmentation enables more reproducible volumetric analysis and quantification of TAV and PAV that are established end points in longitudinal studies assessing the efficacy of novel pharmacotherapies. Therefore, it should be preferred over conventional IVUS analysis as its higher reproducibility is expected to have an impact on the sample size calculation for the primary end point.